Investigations of characteristics of metal film based pyroelectric detectors implanted by Ar+ ions - Lysyuk, V.O.; Poperenko, L.V.; Staschuk, V.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
Functional parameters and characteristics of pyroelectric detectors based on the system thin metal film - thick pyroelectric substrate are investigated. Such metals as Ni, Mo and Ti were used to increase absorption of such systems. The pyroelectric substrates (LiNbO₃ and LiTaO₃) with thickness of 0.1 mm coated by metal films with thicknesses of 15-40 nm were investigated. Influence of ion implantation on functional characteristics (radiation stability, adhesion) of pyroelectric detectors developed on the base of such systems are shown. Application of such pyroelectric detectors to registration of power laser radiation is proposed.